Antivenom against Crotalus durissus terrificus venom: Immunochemical reactivity and experimental neutralizing capacity - Baudou, Federico Gastón (2017)
Fil: Baudou, Federico Gastón. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos. Área Investigación Desarrollo / Venenos; Argentina.